1999
DOI: 10.1101/gad.13.11.1361
|View full text |Cite
|
Sign up to set email alerts
|

FGF signaling inhibits chondrocyte proliferation and regulates bone development through the STAT-1 pathway

Abstract: Several genetic forms of human dwarfism have been linked to activating mutations in FGF receptor 3, indicating that FGF signaling has a critical role in chondrocyte maturation and skeletal development. However, the mechanisms through which FGFs affect chondrocyte proliferation and differentiation remain poorly understood. We show here that activation of FGF signaling inhibits chondrocyte proliferation both in a rat chondrosarcoma (RCS) cell line and in primary murine chondrocytes. FGF treatment of RCS cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
259
3
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(280 citation statements)
references
References 28 publications
15
259
3
3
Order By: Relevance
“…Bones formed via either endochondral or intramembranous ossification in Stat1 Ϫ/Ϫ mice have an increase in mass and mineral density due to a disruption in the proliferation and differentiation properties of both osteoblasts and osteoclasts (Kim et al, 2003;Xiao et al, 2004), and FGFs have an anti-proliferative effect on chondrocytes that is disrupted by loss of Stat1 (Sahni et al, 1999(Sahni et al, , 2001.…”
Section: Stat Proteins Act Upstream Of Tcfap2amentioning
confidence: 99%
“…Bones formed via either endochondral or intramembranous ossification in Stat1 Ϫ/Ϫ mice have an increase in mass and mineral density due to a disruption in the proliferation and differentiation properties of both osteoblasts and osteoclasts (Kim et al, 2003;Xiao et al, 2004), and FGFs have an anti-proliferative effect on chondrocytes that is disrupted by loss of Stat1 (Sahni et al, 1999(Sahni et al, , 2001.…”
Section: Stat Proteins Act Upstream Of Tcfap2amentioning
confidence: 99%
“…It has been suggested that hyperactivation of Stat1 might be involved in the growth impairment observed in genetic forms of dwar®sm involving activated mutations in FGF receptor (Su et al, 1997). Primary chondrocytes derived from Stat1-de®cient embryos were found to be defective in FGF-mediated growth inhibition, even though normal levels of FGF receptors were expressed (Sahni et al, 1999). Furthermore, organ cultures of bone rudiments from mouse embryos showed that FGF treatment produces a drastic impairment of chrondrocyte proliferation and bone development in wild-type but not in Stat17/7 bone cultures.…”
Section: Stat1 Growth Control and Cancermentioning
confidence: 99%
“…Missense mutations in the transmembrane region of FGFR3 result in constitutive activation and the autosomal dominant heritable disorders of skeletal development such as thanatophoric dwarfism, achondroplasia and Crouzon syndrome (Tavormina et al, 1995;Naski et al, 1996;Bonaventure et al, 2001). The phenotype observed in dwarfism suggests that the dysregulation of FGFR3 could impair cell growth and differentiation (Su et al, 1997;LegeaiMallet et al, 1998;Sahni et al, 1999), knockout mouse studies confirming an inhibitory role for FGFR3 in bone growth (Colvin et al, 1996;Deng et al, 1996). However, FGFR3 may regulate differentiation (Kobrin et al, 1993;Kanai et al, 1997) or apoptosis (Plowright et al, 2000) dependent on the tissue type, consistent with a multifunctional role of FGFR3.…”
mentioning
confidence: 93%